Poly-IC enhances the effectiveness of cancer immunotherapy by promoting T cell tumor infiltration. Issue 2 (21st September 2020) - Sultan, Hussein; Wu, Juan; Fesenkova, Valentyna I; Fan, Aaron E; Addis, Diane; Salazar, Andres M; Celis, Esteban
Abstract : Background: Immunotherapies, such as immune checkpoint inhibitors and adoptive cell therapies, have revolutionized cancer treatment and resulted in complete and durable responses in some patients. Unfortunately, most immunotherapy treated patients still fail to respond. Absence of T cell infiltration to the tumor site is one of the major obstacles limiting immunotherapy efficacy against solid tumors. Thus, the development of strategies that enhance T cell infiltration and broaden the antitumor efficacy of immunotherapies is greatly needed. Methods: We used mouse tumor models, genetically deficient mice and vascular endothelial cells (VECs) to study the requirements for T cell infiltration into tumors. Results: A specific formulation of poly-IC, containing poly-lysine and carboxymethylcellulose (PICLC) facilitated the traffic and infiltration of effector CD8 T cells into the tumors that reduced tumor growth. Surprisingly, intratumoral injection of PICLC was significantly less effective in inducing tumor T cell infiltration and controlling growth of tumors as compared with systemic (intravenous or intramuscular) administration. Systemically administered PICLC, but not poly-IC stimulated tumor VECs via the double-stranded RNA cytoplasmic sensor MDA5, resulting in enhanced adhesion molecule expression and the production of type I interferon (IFN-I) and T cell recruiting chemokines. Expression of IFNαβ receptor in VECs was necessary to obtain the antitumor effects by PICLC and IFN-I was found to directly stimulate the secretion of T cell recruiting chemokines by VECs indicating that this cytokine-chemokine regulatory axis is crucial for recruiting effector T cells into the tumor parenchyma. Unexpectedly, these effects of PICLC were mostly observed in tumors and not in normal tissues. Conclusions: These findings have strong implications for the improvement of all types of T cell-based immunotherapies for solid cancers. We predict that systemic administration of PICLC will improve immune checkpoint inhibitor therapy, adoptive cell therapies and therapeutic cancer vaccines.